Perencanaan Strategis Sistem Informasi Menggunakan Metodologi Ward and Peppard Pada Putra Darmawan Travel Salatiga - Ricky Malau; Penidas Fodinggo Tanaem (APTIKOM SUMSEL, 2022)
Putra darmawan travel is a company engaged in transportation services, located on Jalan Diponegoro No 64, Sidorejo, Salatiga City, Central Java. This company provides travel services, tours, car loans, and express packages. However, in carrying out its business business, this company has not yet applied SI / IT in its company operations, so he recommends to carry out strategic planning of information systems, aiming to assist in the preparation of information systems so that later they can have benefits and be in line with the goals and business processes that exist in the company. The preparation of the strategic design of this information system uses the ward and peppard method, with this method will be carried out several analyzes on the sons of travel darmawan in order to assist in the preparation of information system designs such as SWOT analysis, Value Chain, Five Porter's, Mc Farlan Strategic Grid whose output is in the form of proposed application portfolio recommendations in the form of Making SI Web travel, SI Promotion, SI Cashier, Asset Sim, which can be used as a reference for the putra darmawan travel company to be applied within the next 2-5 years